Rechargeable aqueous ZnIS flow battery system
By developing the colloid chemistry of iodine-starch cathode electrolyte in aqueous zinc-iodine flow batteries, the problems of low operating current density and mutual series penetration of Zn-I FB are solved, and high-efficiency and low-cost energy storage effects are achieved.
Patent Information
- Application Number
- CN202410846872.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-17
- Filing Date
- 2024-06-27
- Publication Date
- 2025-02-21
AI Technical Summary
Aqueous zinc-iodine flow cells (Zn-I FB) are hindered by low operating current density and poor power density in large-scale energy storage, and the inter-serial penetration of iodine-active materials leads to capacity loss and low Coulomb efficiency.
By adopting electrolyte engineering strategies, the colloid chemistry of iodine-starch cathode electrolyte is developed, the colloid aggregation induced by chemical adsorption, and the size of active materials is increased, thereby solving the relevant challenges of Zn-I FB.
The Zn-I FB system with high ion selectivity and high ionic conductivity is achieved, which improves Coulomb efficiency, voltage efficiency and energy efficiency, and significantly reduces the installation cost of the battery.
Smart Images

Figure CN119495781A_ABST
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to U.S. patent application No. 18 / 451,132 filed on August 17, 2023, and the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0002] The present invention relates generally to the fields of colloid chemistry, nanoparticle technology, battery technology and energy storage. More specifically, the present invention provides a rechargeable aqueous zinc||iodine-starch flow battery. Background Art
[0003] Energy storage plays a vital role in enhancing the utilization efficiency of clean and renewable energy sources such as wind and solar energy. Among various energy storage technologies, flow batteries stand out as a promising option for large-scale storage due to their low cost and high power characteristics. Aqueous zinc-iodine flow batteries (Zn-I FBs) have been widely used due to their inherent safety, high theoretical specific capacity (268Ah L- 1 Unfortunately, the utilization of Zn-I FBs for large-scale energy storage is hampered by low operating current density and poor power density.
[0004] At present, Zn-I FB faces typical bottleneck problems: First, due to limited ionic conductivity and significant overpotential, the widespread use of Nafion membrane systems leads to low power density. Fluorinated Nafion-based membranes are expensive, resulting in higher total battery costs. Even though dense Nafion-based membranes can enhance selectivity to improve coulombic efficiency (CE), the dense Nafion-based membranes may cause a compromise in ionic conductivity, resulting in increased membrane resistance and impaired voltage efficiency (VE) and energy efficiency (EE), especially at high operating currents. Therefore, Zn-I FB systems generally have low power density. Secondly, the iodine active material (I x - ) leads to severe cross-penetration problems in porous membrane systems, resulting in capacity loss and low Coulombic efficiency.
[0005] To overcome these challenges, membrane modification and / or electrolyte engineering have been identified as potential solutions for Zn-I FBs. Regarding membrane modification, the main improvement strategies focus on introducing membrane coatings characterized by ion screening and / or charge repulsion effects to prevent the interpenetration of active species. However, these membrane coating strategies will inevitably face the problem of increased internal resistance and increased overpotential. Therefore, membrane coating strategies may not improve energy efficiency. In addition, the design of new polymer membranes is hindered by the challenges of achieving precise pore size regulation, controllable thickness, and specific surface charge state of the membrane. To address this problem, low-cost polyolefin-based porous membranes (LPPMs) have become promising separators for enhancing working currents due to their high ion permeability and low ionic resistance. Although low-cost polyolefin-based porous membranes can effectively enhance membrane-based ionic conductivity and increase working currents, they still face the problem of significant interpenetration of iodine cathode electrolytes, resulting in capacity loss and reduced Coulombic efficiency.
[0006] With regard to electrolyte engineering, the development of large-sized iodine-based catholytes has great potential to simultaneously maintain high ion selectivity and high ionic conductivity suitable for porous membranes of specific pore sizes. However, electrolyte engineering strategies to achieve this goal remain to be developed. Summary of the invention
[0007] The present invention aims to develop the colloidal chemistry of iodine-starch catholyte, thereby imparting active materials of increased size through strong chemisorption-induced colloidal aggregation.
[0008] Therefore, the present invention aims to address the challenges associated with aqueous zinc-iodine flow batteries (Zn-IFBs) by employing an electrolyte engineering strategy.
[0009] In a first aspect, the present invention provides a rechargeable aqueous Zn||IS flow battery system. The flow battery system comprises a cathode side, the cathode side comprising an electrode material and a first storage tank providing a cathode electrolyte; an anode side, the anode side comprising the electrode material and a second storage tank providing an anolyte; and a diaphragm positioned between the cathode and the anode. The anolyte and the catholyte flow between the cathode and the anode via a peristaltic pump. When the rechargeable aqueous Zn||IS flow battery system is in a charged state, the electrode material on the cathode side absorbs and stores one or more ions from the cathode electrolyte, and the electrode material on the anode side absorbs and stores one or more ions from the anolyte.
[0010] According to one embodiment, the electrode material comprises carbon felt.
[0011] According to one embodiment, the geometric area of the carbon felt is 4.0 cm 2, and the thickness is in the range of 1-5 mm.
[0012] According to one embodiment, the average diameter of the aggregated colloidal nanoparticles is in the range of 120-140 nanometers.
[0013] According to one embodiment, the anolyte comprises zinc chloride.
[0014] According to one embodiment, the catholyte is prepared with 2M ZnI2 and 0.1 to 2M soluble starch dissolved in deionized water, and the anolyte is prepared with deionized water containing 2M ZnCl2.
[0015] According to one embodiment, the separator comprises a porous polypropylene membrane.
[0016] According to one embodiment, the rechargeable aqueous Zn||IS flow battery system further comprises PTFE end plates, PTFE chambers, PTFE gaskets, PTFE liners, PTFE tubes, carbon plates, and Ti foils.
[0017] According to one embodiment, the total internal resistance of the rechargeable aqueous Zn||IS flow battery system is less than 1Ωcm 2 .
[0018] According to one embodiment, the power density of the rechargeable aqueous Zn||IS flow battery system is at least 40 mW cm -2 .
[0019] According to one embodiment, the rechargeable aqueous Zn||IS flow battery system has a current range of 7.5 to 30 mA cm at room temperature. -2 The invention discloses a novel nanostructured carbon nanotube having a coulombic efficiency of at least 94%, a voltage efficiency of at least 75% and an energy efficiency of at least 74% at a current density of 1.5 Å.
[0020] According to one embodiment, the rechargeable aqueous Zn||IS flow battery system has a high efficiency in the range of 7.5 to 30 mA cm at an elevated temperature of 50°C. -2 The invention discloses a novel nanostructured carbon nanotube having a coulombic efficiency of at least 90%, a voltage efficiency of at least 75% and an energy efficiency of at least 74% at a current density of 100 Å.
[0021] According to one embodiment, the rechargeable aqueous Zn||IS flow battery system is -2 The cycle stability of 350 cycles was achieved.
[0022] According to one embodiment, the rechargeable aqueous Zn||IS flow battery system performs at 32.4Ah L at an elevated temperature of 50°C. -1The cycling stability of 200 cycles was achieved at a high volumetric capacity.
[0023] In a second aspect, the present invention provides a wind and photovoltaic power generation system comprising the rechargeable aqueous Zn||IS flow battery system of the present invention.
[0024] The present invention relates to adjusting the size of charged iodine in the cathode electrolyte based on the size sieving effect of the specific pore size of the porous membrane. Following the size sieving rule, high ion selectivity and high ionic conductivity of the IS cathode electrolyte are achieved simultaneously. In this case, the Zn-IS FB based on the colloidal IS can deliver high reversibility and superior performance, with a Coulombic efficiency of at least 95% and a high current density of at least 30 mAh cm -2 , power density of at least 40 mW cm -2 and a stable cycling stability of approximately 350 cycles. In addition, the scaled-up flow battery module demonstrated its potential as an integrated renewable energy storage system in combination with photovoltaic solar arrays.
[0025] Compared with the prior art, the present invention has significant advantages, including: (a) Starch-based colloidal electrolytes have extremely simple preparation processes, low cost, and minimal environmental pollution; (b) Starch-based colloidal electrolytes exhibit remarkable high-temperature performance, up to 50 °C; (c) The present invention can realize a renewable energy storage integrated system between scaled-up liquid flow battery modules and photovoltaic solar arrays. (d) The present invention provides high power output due to the utilization of low-cost membranes, and the installation cost of a 1-MW flow stack is significantly reduced to only 7% of the cost, compared to the installation cost of a 1-MW conventional Nafion membrane, which is approximately 14.3 times lower. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Embodiments of the present invention are described in more detail below with reference to the accompanying drawings, in which:
[0027] Figure 1 a) shows a schematic illustration of a zinc-iodine flow battery (Zn-I FB) without cross-linking at room temperature and high temperature. b) shows the polyiodide (I x - ) leads to severe cell discharge in conventional Zn-I FBs. c) Schematic illustration of how electrolytes based on colloid chemistry limit the size of active materials (I x - )'s schematic illustration of the interpenetration;
[0028] Figure 2 The chemical and molecular structure of starch is shown;
[0029] Figure 3A Blank starch solution (1 M), blank polyiodide (I x - ) solution (0.01 M) and starch (1 M) x - Digital image of solution (0.01 M). Figure 3B The viscosity, ionic conductivity and I of 2 M ZnI2 electrolyte with different starch concentrations are plotted. x - Permeability. Figure 3C The size distribution of colloidal particles in blank starch solution and 50% SOC starch are depicted respectively. Figure 3D The Raman spectra of starch / polyiodide complex at different SOCs are depicted; Figure 3E The I5 of blank 2M ZnI2 and ZnI2 containing 1M starch at different SOCs is plotted. - With 13 - The calculated ratio between . Figure 3F I3 is shown - and I5 - evolution of bonding energy for interactions with soluble starch;
[0030] Figure 4 Photographs of different concentrations of starch in 2M ZnI2 are shown;
[0031] Figure 5 A model for ion permeation measurements is shown;
[0032] Fig. 6A The UV-visible spectra of KI3 at various concentrations are shown. Figure 6B Beer's law plot of I3-fold concentrations between 0.1 mM and 1 mM is shown;
[0033] Figure 7 The KI3 permeate solution through the PP membrane, UV-vis on the KI3 permeate side, and the permeation rate of KI3 through the PP membrane under blank 2MKI3 electrolyte are shown;
[0034] Figure 8 The results show that the 2M KI electrolyte containing 0.1M starch x KI through PP film x Osmotic solution, KI x UV-vis and KI on the permeate side x Permeability through PP membrane;
[0035] Fig. 9 The results show that the 2M KI electrolyte containing 0.2M starch x KI through PP film x Osmotic solution, KI x UV-vis and KI on the permeate side x Permeability through PP membrane;
[0036] Fig.10 It was shown that in 2M KI containing 0.5M starch electrolyte x KI through PP film x Osmotic solution, KI x UV-vis and KI on the permeate side x Permeability through PP membrane;
[0037] Fig.11 The results show that the 2M KI electrolyte containing 1M starch x KI through PP film x Osmotic solution, KI x UV-vis and KI on the permeate side x Permeability through PP membrane;
[0038] Fig.12 The results show that the 2M KI electrolyte containing 2M starch x KI through PP film x Infiltration solution, KI x UV-vis and KI on the permeate side x Permeability through PP membrane;
[0039] Fig.13 The results show that the 2M KI electrolyte containing 3M starch x KI through PP film x Infiltration solution, KI x UV-vis and KI on the permeate side x Permeability through PP membrane;
[0040] Fig.14 AFM images of 1 M starch solutions are shown;
[0041] Fig.15 The particle size distribution of 1M starch is depicted;
[0042] Fig.16 Depicted is a 1 M starch solution with I x - AFM images of the interaction in 50% SOC.
[0043] Fig.17 Shown is 1M starch with I x -Particle size distribution at 50% SOC;
[0044] Fig.18 The nitrogen adsorption / desorption curves of PP membranes are depicted. The inset is the pore size distribution;
[0045] Fig.19 Plotted is I3 with / without starch at 50% SOC - and I5 - I 3d XPS depth curve of species;
[0046] Fig. 20 Electrostatic potential (ESP) mapping of starch molecules is shown;
[0047] Fig.21 A 2×2 cm flow battery cell is shown for testing. 2 photographs of battery cell assemblies of battery cells;
[0048] Fig.22A The results show that the hysteresis curves at 7.5, 15, 22.5, 30 and 37.5 mA cm 2 Zn-IS FB (2 ml 2M ZnI2 containing 1M starch || PP membrane || 8 ml 2M ZnCl2, 4 cm 2 CE, VE and EE of membrane area). Fig. 22B The results show that the hysteresis curves at 7.5, 15, 22.5, 30 and 37.5 mA cm 2 Voltage curve of Zn-IS FB under . Fig. 22C The polarization of Zn-IS FB using different membranes is depicted. Fig.22D The Zn-I FB system is characterized at high power density (30 mA cm 2 ). The inset is the corresponding voltage curve. Fig.22E The plot is at 22.5 mA cm -2 At a current density of 50% SOC, 36Ah L -1 ) Cycling performance of Zn-I FB system with / without starch. The inset is the corresponding voltage curve;
[0049] Fig.23 The results show that the kinetics of ... 2 Zn-IS FB (2 ml 2M ZnI2 containing 1M starch || PP membrane || 8 ml 2M ZnCl2, 4 cm 2 Membrane area) of the constant current cycle;
[0050] Fig.24The voltage curves of Zn-IFB using starch-free N117 membrane at different current densities are depicted;
[0051] Fig.25 The EIS of Zn-IFBs using different membranes (PP membrane with 1 M starch and N117 membrane without starch) at charge to 30 mAh are depicted;
[0052] Fig.26A The plot is at 22.5 mA cm -2 Cycling performance of the Zn-I FB system using starch-free PP film at high volumetric capacity. Fig.26B The volumetric capacity versus voltage corresponding to cycles 18 to 23 is plotted, with the short-circuit point and cross-talk marked. Fig.26C The volumetric capacity versus voltage corresponding to cycles 54 to 56 is plotted, with the short-circuit point and cross-link penetration marked;
[0053] Fig.27A Galvanostatic cycling of Zn-IFBs using N117 membrane at high volumetric capacity is depicted. Fig.27B The plot is at 22.5 mA cm -2 High volume capacity (33.5Ah L -1 ) under the cycling performance of Zn-I FB system using starch-free PP film. Fig.27C The volumetric capacity versus voltage corresponding to cycles 41 to 44 is plotted, with soft shorts, hard shorts, and crosstalk penetration marked. Fig.27D The volumetric capacity and voltage corresponding to cycles 106 to 144 are plotted, with soft short circuits, severe short circuit points, and cross-link penetration marked;
[0054] Fig.28A shows that after 30 cycles at 22.5 mA cm -2 and 33.5Ah L -1 SEM image of the original CF in the discharged state, Fig.28B shows that after 30 cycles at 22.5 mA cm -2 and 33.5Ah L -1 SEM image of the CF anode using PP film without starch in the discharged state. Fig.28C shows that after 30 cycles at 22.5 mA cm -2 and 33.5Ah L -1 SEM image of CF anode using PP film containing starch at the discharge state;
[0055] Fig.29The XRD patterns of pristine CF, CF using PP film without starch, and CF using PP film containing starch are depicted;
[0056] Fig. 30A shows that after 30 cycles at 22.5 mA cm -2 and 33.5Ah L -1 SEM image of the original PP film in the discharged state. Fig. 30B shows that after 30 cycles at 22.5 mA cm -2 and 33.5Ah L -1 SEM image of the cycled PP film without starch under the discharged state. Fig. 30C shows that after 30 cycles at 22.5 mA cm -2 and 33.5Ah L -1 SEM image of the cycled PP film containing starch under the discharged state.
[0057] Fig.31 The XRD patterns of pristine PP and PP films after cycling with / without starch are depicted;
[0058] Fig.32 shows that after 30 cycles at 22.5 mA cm -2 and 33.5Ah L -1 SEM image of CF anode using N117 membrane without starch at the discharged state.
[0059] Fig.33A Shown is a SEM image of pristine N117 on the anode side. Fig.33B SEM images of N117 membrane without starch on the anode side are shown;
[0060] Fig.34A and Fig.34B The results show that the 30-cycle -2 and 33.5Ah L -1 XRD patterns of pristine N117 film and N117 film without starch on the anode side and CF anode using N117 film without starch at the discharge state of ;
[0061] Fig.35A The results show that the 7.5, 15, 22.5, 30 and 37.5 mA cm 2 CE, VE and EE of Zn-I FB under . Fig.35B The results are plotted at 77.5, 15, 22.5, 30, and 37.5 mA cm 2 Voltage curve of Zn-IS FB under . Fig.35CThe polarization of the Zn-IS FB using PP film at high temperature (50 °C) is depicted. Fig.35D The Zn-IS FB system is characterized at high power density (30 mA cm 2 ) and high temperature (50℃) cycling performance. The inset is the corresponding voltage curve. Fig.35E The plot is at 22.5 mA cm -2 Cycling performance of Zn-IS FB system with / without starch at high volumetric capacity (35.5Ah L-1) and high temperature (50℃) at current density. The inset is the corresponding voltage curve;
[0062] Fig.36 Galvanostatic cycling of Zn-IS FB at different current densities at high temperature (50 °C) is depicted;
[0063] Fig.37A The cycling performance of the Zn-I FB system using starch-free PP film at high volumetric capacity is depicted. Fig.37B The volumetric capacity versus voltage corresponding to cycles 6 to 9 is plotted, with the short-circuit point and cross-talk penetration marked. Fig.37C The volumetric capacity versus voltage corresponding to cycles 21 to 24 is plotted, with the short-circuit point and cross-talk penetration marked;
[0064] Fig.38 A 5×5 cm flow battery cell test is shown. 2 A photograph of the battery cell assembly of the battery cell; and
[0065] Fig.39A Shown are the one-day light intensity (top) and charging current density (bottom) data of a renewable energy storage demonstration system based on a large-scale Zn-IS FB. Fig.39B Depicted is the power generated by a solar photovoltaic cell with a capacity of 20 mAh cm -2 Discharge voltage curve of a large-scale Zn-ISFB flow battery cell after one day of charging. Fig.39C A solar cell energy storage system is shown during the day and at night. Fig.39D and Fig.39E A cost analysis based on a 1 MW Zn-IFB flow stack based on Nafion 117 membrane and PP with starch additive is shown. DETAILED DESCRIPTION
[0066] The present invention will also be described in detail by the following examples and accompanying drawings. It should be understood that the specific embodiments are provided only for illustrative purposes and should not be interpreted in a limiting manner. It will be appreciated by those skilled in the art that the present invention described herein may be modified and altered in addition to those specifically described.
[0067] The present invention includes all such changes and modifications. The present invention also includes all steps and features mentioned or indicated in this specification individually or collectively, and any and all combinations or any two or more steps or features in the steps or features. Other aspects and advantages of the present invention will be apparent to those skilled in the art by reviewing the subsequent description.
[0068] Traditionally, research has focused on membrane modification to enhance the performance of Zn-IFBs. However, such strategies may face challenges associated with the high cost and precise synthesis of nanostructured materials with the desired sieving size and specific charge loading. Figure 1 As shown in a) and b), the original LPPM will inevitably show low selectivity for active materials, especially for charged iodine species, leading to irreversibility on the cathode side and severe cross-linking and capacity loss. At the same time, the cross-linking problem of the cathode electrolyte may be exacerbated, especially when the Zn-IFB is integrated with renewable power energy (e.g., solar and wind energy) and operated in a high-temperature outdoor environment.
[0069] To address the limitations of the original LPPM, functional coatings can be introduced that are designed to provide ion sieving confinement and / or charge repulsion effects, thereby effectively preventing the interpenetration of redox species. However, implementation of this strategy may result in increased ionic resistance and encounter challenges associated with the high cost and precise synthesis of nanostructured materials with specific sieving sizes and specified load charges. Based on the principle of size sieving effects in LPPM, there is the potential to enhance the selectivity of these membranes by adjusting the size of the active materials, specifically the charged iodine species in the electrolyte.
[0070] Therefore, in a first aspect, the present invention provides a rechargeable aqueous Zn||IS flow battery system. The flow battery system comprises a cathode side, the cathode side comprising an electrode material and a first storage tank providing a cathode electrolyte; an anode side, the anode side comprising the electrode material and a second storage tank providing an anolyte; and a diaphragm, the diaphragm being positioned between the cathode and the anode. The anolyte and the catholyte flow between the cathode and the anode via a peristaltic pump. When the rechargeable aqueous Zn||IS flow battery system is in a charging state, the electrode material on the cathode side absorbs and stores one or more ions from the catholyte, and the electrode material on the anode side absorbs and stores one or more ions from the anolyte. It proposes an extremely simple modification method for improving a Zn-I flow battery system. Based on the size sieving effect, the starch-containing colloid chemistry can enhance the selectivity of polyiodides, thereby enabling the use of low-cost porous membranes with superior ionic conductivity suitable for Zn-I FBs.
[0071] The present invention introduces a novel colloid chemistry for the iodine catholyte of Zn-IFB by introducing renewable and cost-effective starch into the catholyte. Figure 2 As shown, starch is a long-chain polymer containing sugar molecules connected by glycosidic bonds. Soluble straight-chain starch molecules have a linear polymer structure that can be dissolved in water and form hydrogen bonds with water molecules, thereby forming a colloidal solution. The interaction between starch and iodine is attributed to the electron-donating properties of the hydroxyl functional group. These hydroxyls (-OH) can donate electrons to other atoms through covalent bonds or hydrogen bonds. In the iodine-starch complex, the iodine atom forms a complex with the hydroxyl group of the starch molecule, resulting in a strong chemical interaction between the oxygen atom of the hydroxyl group and the iodine atom, thereby contributing to the stability of the complex.
[0072] IS-based active materials in the catholyte can be tuned into aggregated colloidal nanoparticles, thereby following size sieving rules. This tuning enables the simultaneous realization of high ion selectivity and ion conductivity of the IS catholyte. Figure 1 In (c), electrolyte regulation is used to increase the size of the active iodine species, thereby making the active iodine species larger than the pore size of the applied LPPM, ideally eliminating the problem of interpenetration of charged iodine species. At the same time, the size of the active iodine species should not be too large to result in low diffusion efficiency or even precipitation. Matching the size of the active iodine species with the pores of the LPPM is a challenge, and such regulation strategies have not yet been developed. Forming large-sized colloidal iodine-starch (IS) active species has great potential to avoid active redox losses caused by LPPM.
[0073] In one of the embodiments, the catholyte comprises zinc iodide (ZnI2) and soluble starch that together form an electrolyte having aggregated colloidal nanoparticles. The anolyte comprises zinc chloride.
[0074] The catholyte is prepared with 2M ZnI2 and 0.1 to 2M soluble starch dissolved in deionized water, while the anolyte is prepared with deionized water containing 2M ZnCl2. Preferably, the concentration of soluble starch is 1M.
[0075] In one embodiment of the embodiment, the electrode material can be carbon felt. The geometric area of the carbon felt is 4.0 cm 2 , and the thickness is in the range of 1-5 mm. For example, the thickness of the carbon felt is 1 mm, 2 mm, 3 mm, 4 mm or 5 mm.
[0076] In one of the embodiments, the separator may be a porous polypropylene membrane.
[0077] In one embodiment of the embodiment, based on the colloid aggregation effect with strong chemical adsorption, the iodine-starch (IS) colloid is configured to have an increased size. The size screening effect effectively suppresses the iodine interpenetration, so that the porous PP film with excellent ionic conductivity can be utilized. The average diameter of the aggregated colloidal nanoparticles is in the range of 120-140 nanometers. Preferably, the average diameter of the aggregated colloidal nanoparticles is about 134 nanometers.
[0078] In another embodiment, the rechargeable aqueous Zn||IS flow battery system further comprises a PTFE end plate, a PTFE chamber, a PTFE gasket, a PTFE liner, a PTFE tube, a carbon plate, and a Ti foil.
[0079] In one embodiment, the total internal resistance of the rechargeable aqueous Zn||IS flow battery system is less than 1Ωcm 2 For example, the total internal resistance of the rechargeable aqueous Zn||IS flow battery system is 0.91 Ωcm 2 .
[0080] In one embodiment of the embodiments, the power density of the rechargeable aqueous Zn||IS flow battery system is at least 40 mW cm -2 .
[0081] In one embodiment of the present invention, the rechargeable aqueous Zn||IS flow battery system can be used in the range of 7.5 to 30 mA cm at room temperature. -2The rechargeable aqueous Zn||IS flow battery system exhibits a coulombic efficiency of at least 94%, a voltage efficiency of at least 75%, and an energy efficiency of at least 74% at a current density of 1.5 to 30 mA cm -2 The invention discloses a novel nanostructured carbon nanotube having a coulombic efficiency of at least 90%, a voltage efficiency of at least 75% and an energy efficiency of at least 74% at a current density of 100 Å.
[0082] In one of the embodiments, the Zn-IS FB based on colloidal IS with polypropylene (PP) film as LPPM was 30 mA cm -2 It exhibits excellent cycling stability for 350 cycles.
[0083] In one embodiment of the present invention, the Zn-IS FB based on colloidal IS with polypropylene (PP) film was 32.4 Ah L -1 The battery exhibits excellent cycling stability of 200 cycles even at a high temperature of 50°C at a high volumetric capacity of 1.5 % (50% charged state).
[0084] In one of the embodiments, the installation cost of a 1-MW flow stack can be significantly reduced by 14.3 times compared to the installation cost of a Nafion membrane.
[0085] In a second aspect, the present invention provides a wind and photovoltaic power generation system comprising the rechargeable aqueous Zn||IS flow battery system of the present invention.
[0086] A scaled-up flow battery module has been successfully integrated with a photovoltaic solar array to create a renewable energy storage system. This significant achievement opens a new frontier in the development of colloidal electrolyte chemistry for LPPM-based flow battery systems, enabling low-cost, high-power, and high-temperature flow batteries for large-scale energy storage applications.
[0087] The following examples illustrate the present invention but are not intended to limit the present invention.
[0088] Examples
[0089] Example 1 - Materials and Methods
[0090] Material
[0091] All chemicals were used as received. Zinc iodide (ZnI2, ≥99.99%), zinc chloride (ZnCl2, ≥99.99%), starch soluble ((C6H 10O5)n, ≥99%), potassium iodide (KI, ≥99%), potassium hydroxide (KOH, ≥8%), sulfuric acid (H2SO4, 95%-98%), hydrogen peroxide (H2O2, 30wt% in H2O), iodine (I2, ≤99%) were purchased from Sigma-Aldrich. Graphite felt (3.0 mm, carbon ≥99%, bulk density 0.12-0.14 g cm -2 ) was purchased from Yi Deshang Carbon Technology. Nafion membrane (N117, Dupont) was purchased from Shanghai Hesen Electric. Polypropylene (PP) membrane (Celgard2325) was purchased from Suzhou Sinoro Technology. Ti mesh (99.9%, 100 mesh) was obtained from Kangwei Metal. Zn foil (200 μm, 99.99%) was purchased from Chenshuo Metal.
[0092] Material properties
[0093] The crystal structure was studied by X-ray diffraction (XRD, X'Pert Pro MPD of Philips, Holland) using CuKα as the radiation source at 40 kV and 40 mA. The morphology was detected by scanning electron microscopy (SEM, FEIQuanta 450FEGSEM). X-ray photoelectron spectroscopy (XPS) spectra were recorded on a photoelectron spectrometer (ESCALAB 250, Thermo Scientific, America), where the binding energy (BE) of the element was calibrated by the BE of C 1s (284.60 eV). Modulus mapping was measured by atomic force microscopy (Bruker, DIMENSION ICON) and performed in quantitative nanomechanical mode (QNM). Raman measurements (Dxr-2xi, Thermo Scientific, USA) were performed with an in-situ homemade battery cell to observe the OH stretching peak. A pH meter (brand: REX, model: PHBJ-26IL) was used to monitor pH changes.
[0094] Zn 2+ Preparation of ion exchange membrane
[0095] Zn 2+ Nafion membrane (N117, from DuPont, USA, with an effective area of 9 cm 2) was pretreated by the following steps before use. First, the Nafion membrane was soaked in a 3 wt % H2O2 aqueous solution at 80°C for 1 hour. The membrane was rinsed with deionized (DI) water to remove the remaining H2O2. Second, the Nafion membrane was soaked in 0.5 M H2SO4 at 80°C for 1 hour and rinsed with DI water until the pH in the effluent was close to 7. Finally, it was soaked in a 1 M ZnCl2 aqueous solution (the pH was adjusted to 1 by using HCl) at 60°C for 3 hours to remove the H2O2. + Type converted to Zn 2+ The membrane was then rinsed with DI water and stored in DI water.
[0096] Density functional theory (DFT) calculations
[0097] Electrostatic potential (ESP) mapping was performed using the Gaussian 09W software package to obtain the structural information of the molecules mentioned above. The geometry optimization used the B3LYP method with a 6-31+G(d, p) basis set. Based on the optimized molecular structure, ESP analysis of the van der Waals surface was performed using the Multiwfn 3.3.8 software package in the Gaussian 09W software package to deduce possible soluble starch functional sites. Zn 2+ , Cl - ,I - 、I3 - or I5 - The structure of soluble starch and its complex (starch @ Zn 2+ 、Starch@Cl - , starch@I - 、Starch@I3 - or starch @I5 - ) were first optimized at the B3LYP / def2-TZVP level by using density functional theory (DFT). All geometry optimizations were performed in ORCA using the DFT-D3 method, including an implicit solvent model with SMD. The single point energies of the complexes were then optimized at the same level after the previous optimizations, taking into account the basis set superposition error (BSSE). Harmonic frequency calculations were performed at the same level of theory to help verify that all structures were free of imaginary frequencies.
[0098] The binding energy of the configuration (E bind ) is calculated by the following equation: E bind =E AB -(E A +E B ) (3), Where E A 、E Band E AB Respectively represent A(I3 - or I5 - ) and B (soluble starch) and the energy of the complex, E bind Negative values of indicate that the process is an exothermic reaction, and high negative values correspond to stronger interactions, thereby indicating more heat release and more stable products.
[0099] Electrochemical characterization
[0100] CV and CA tests were performed on an electrochemical workstation (CHI 760E) with a three-electrode system, in which a glassy carbon electrode (6 mm in diameter) was used as a working electrode, a platinum plate was used as a counter electrode, and a saturated calomel electrode (SCE) was used as a reference electrode in the electrolyte. The working potential was operated with stirring and the test was performed within -0.4 to 1.2 V relative to SCE. The CA test was performed at a constant potential of 1.2 V relative to SCE.
[0101] EIS measurements were performed on a CHI electrochemical test cell (760E). Sinusoidal voltage oscillations with an amplitude of 10 mV at the OCV of the cell were collected before testing. The oscillation frequency ranged from 1,000 kHz to 100 mHz, with each test repeated three times. The internal resistance of the FB was determined by different current densities (10–40 mA cm -2 ), where the FB after being charged to 50% SOC was charged and discharged at different current densities for 1 min.
[0102] The constant current characteristics of the Zn-IFB cells were tested on a battery test system (LAND, CT2001A) at room temperature (23–25 °C, unless otherwise specified) or in an incubator at elevated temperature (50 °C). The current density was set between 7.5 and 37.5 mA cm -2 The charge process was limited by a constant capacity (30 mAh or 71 mAh) and the discharge process was limited by a critical voltage of 0.1 V. The theoretical capacity was calculated with the catholyte (iodide portion), which is the capacity limiting side of the full cell. The catholyte was adjusted to a final volume of 2 mL to provide an electron concentration of 4 M (1 M charge density has a capacity of 26.8 mAh mL-1). 1 , totaling 214.4mAh).
[0103] Example 2 - Preparation of starch-containing colloidal electrolyte
[0104] In one example, the preparation of colloidal iodine-starch in the cathode electrolyte of a battery involves the following steps. First, iodine (I2) is dissolved in water to form an iodine solution. This solution contains charged iodine species (I3-) and uncharged iodine molecules (I2). Next, starch molecules form a complex with the charged iodine species (I3-). Hydrogen bonds are formed between the oxygen atoms in the starch and the iodine species, resulting in a close association between iodine and starch. Due to the complexation between starch and the charged iodine species, iodine-starch (IS) colloids are formed. These colloids are composed of large-sized polymer particles.
[0105] Electrolytes based on colloid chemistry can tune the size of iodine-starch (IS) based redox active materials as aggregated colloidal nanoparticles in the catholyte, thereby suppressing the interpenetration problem to improve the capacity retention.
[0106] Example 3 - Characterization of Starch-Containing Colloidal Electrolytes
[0107] The colloidal Tyndall effect is a phenomenon observed when light is scattered by particles in a colloidal solution or fine suspension. When a beam of light passes through such a solution, it is scattered by the particles in the solution, thus making the path of the light visible. This scattering of light is called the Tyndall effect. Figure 3A As shown in (i), the colloidal Tyndall effect can be observed in 1 M starch solution (M is the molar concentration, expressed in mol L -1 ), indicating that nano-sized colloidal starch is in the range of 1-100 nanometers, which is conducive to the formation of colloidal aggregation. Figure 3A (ii) Bare I without colloidal Tyndall effect x - Compared with solution (0.01M), it is characterized by Figure 3A (iii) I x - and starch mixed solution (0.01MI x - This result can indirectly prove that amylose-type starch can capture polyiodide anions I through strong bonding interactions. x - , thereby forming a starch / polyiodide colloid complex.
[0108] To determine the appropriate concentration of starch-iodine electrolyte, the viscosity, ionic conductivity and permeability of the starch-adjusted electrolyte were studied as important parameters for determining the overall performance of full flow batteries, such as voltage efficiency (VE) and coulombic efficiency (CE).
[0109] like Figure 3Band Figure 4 As shown in Figure 2, the viscosity increases exponentially with increasing starch concentration (from 0 M to 3 M), where the concentration of ZnI2 is fixed at 2 M and M is the molar concentration (in mol L -1 Specifically, the viscosity of the solution containing 1M starch was 13.5 kPa·s, which increased significantly to 227 kPa·s in the electrolyte containing 2M starch (i.e., 20 times that of 1M starch) and more than 100 times that of the electrolyte containing 3M starch (1570 kPa·s). In addition, when the starch concentration increased from 0M to 3M, the ionic conductivity increased from 100.1 mS cm -1 Gradually decreased to 6.5 mS cm -1 In general, higher electrolyte viscosity corresponds to lower ionic conductivity, indicating that viscosity is the main factor of ionic conductivity and 1 M starch in electrolyte can maintain superior ionic conductivity. Figure 5 As shown, the permeation of IS colloids across the PP membrane was evaluated using a two-compartment H cell consisting of a 50% charged state of IS catholyte in one cell and deionized water in the other cell.
[0110] refer to Fig. 6A and 6B , the UV-visible spectrum of KI3 has been tested at various concentrations between 0.1mM and 1mM. Strong peaks at 288 and 350nm are attributed to I3 - The presence of nominally prepared I x - The permeation rate of the solution at different starch concentrations is as follows Figure 7-13 The y axis represents -ln(1-c B / C A ), and the x-axis represents the penetration time. These parameters were used to determine the permeability of KI3 through the PP membrane under blank 2M KI3 and / or 2M KI3 with / without different concentrations of starch. The graph was fitted using a linear fit to obtain -ln(1-c B / c A ) with respect to time (t).
[0111] In more detail, the permeability of KI3 through the PP membrane was determined from the evolution of the UV-visible spectrum on the permeate side in H-cell tests. The feed reservoir was filled with 2M KI3, while the permeate side was filled with deionized water. The two reservoirs had a circularly symmetrical transport channel separated by the PP membrane. It was assumed that the variation of the KI3 concentration in the feed solution reservoir was negligible when its concentration on the permeate side was low and the flux of KI3 through the membrane was constant; that is, pseudo-steady-state conditions existed in both reservoirs during the experiment. where c A and c B (t) are the concentrations of KI3 in the feed side and the permeate side, respectively (mol L -1 ); A and L are the areas of the membrane (cm 2 ) and thickness (cm); V is the volume of the permeate solution (ml); P is the membrane permeability (cm 2 min -1 ); t is the time (minutes), and t0 is the time lag (minutes). The permeability P can be expressed by -ln(1-c B (t) / c A ) with respect to t.
[0112] Compared with the severe permeability in blank electrolyte, I x - The permeability of 2M ZnI2 decreased significantly with increasing starch concentration. This indicates that colloidal starch can strongly confine iodine by forming colloidal aggregates, characterized by low iodine permeability to prevent the cross-penetration problem. Based on these analyses, 1M starch and 2M ZnI2-based IS electrolytes were selected as prototype electrolytes for the following studies.
[0113] Example 4 - Effect of colloid aggregation on particle size
[0114] To investigate the size of the nanoparticles in the colloidal aggregation that matches the pore size of the PP membrane as the LPPM, the microscopic pattern and size were examined using atomic force microscopy (AFM). Figure 3C and Figure 14-15 shows uniform nanoparticles of naked starch colloid on the substrate, the nanoparticles having a distinguishable nanosize of approximately 78.56 nanometers. In contrast, Figure 3C and Figure 16-17 The average size of the starch / polyiodide colloid in the 50% charged state is shown to be 138.49 nm, which is larger than that of the original naked starch. This phenomenon can be attributed to the strong chemical adsorption, thereby promoting the bonding of the colloidal starch molecules containing abundant electron-rich hydroxyl groups with the polyiodide I x - The gathering between.
[0115] According to the size screening rule, it effectively inhibits the permeation rate of IS colloid across the PP membrane with nano-sized pores ( Fig.18 , with an average pore size of 37.28 nm), which reasonably verifies that the starch-containing colloidal electrolyte is beneficial to limit the active materials (polyiodide I x - )’s mutual penetration.
[0116] Example 5 - Interaction between starch and iodine
[0117] refer to Figure 3D-3E The starch / polyiodide complex solutions at different SOC (10%, 20%, 50%, 70%, 100%) were further confirmed by Raman spectra. 120 and 137.16 cm -1 The Raman peak at can be attributed to metal iodide ions (I - ) skeleton vibration, and 110 and 160cm -1 The two Raman peaks at - ) and pentaiodide ion (I5 - ). For the electrolyte without starch, a strong I3 - Signal and weak I5 - signal, and in high charge SOC, I5 - The signal of the species gradually increases with the high content of active redox species. Figure 3D-3E Starch-free system in I3 - The peak showed almost no movement, but I5 - The peaks become broader with decreasing intensity, indicating that the polyiodide complexes are unstable, especially at high concentrations.
[0118] In contrast, by increasing the SOC ratio from 0% to 100% SOC, the I3 - and I5 - Both species showed stable peak signals and obvious blue shift. This indicates that based on the strong chemical bonding of colloidal chemistry, colloidal starch can stabilize the polyiodide active species, i.e., I3 - and I5 - In addition, I5 - The stable existence of species on colloidal starch can also be confirmed by the I3dXPS curve, such as Fig.19 As shown in Figure 2, compared with the blank ZnI2 electrolyte at 50% SOC, I5 - species showed a dominant role in starch-based electrolytes.
[0119] To gain insight into the configurations of IS species, density functional theory (DFT) calculations were performed to investigate the interactions between starch and the main iodine species (I - 、I3 - and I5 - ) and other charge carriers (Zn2 + and Cl - The binding energies of different samples show the following order: starch @I - (Eb=-0.354eV)>Starch@Cl- (Eb=-0.119)>Starch@Zn 2+ (Eb = -0.081 eV). In addition, compared with the blank ZnI2 solution (t + =0.484), the ZnI2 solution containing colloidal starch showed a higher cationic (Zn 2+ ) Migration number (t + =0.651), which can be attributed to the embedding of anions in starch (I - In contrast, the cation migration number of the ZnCl2 aqueous solution containing colloidal starch only slightly increased compared with that of the blank ZnCl2 solution, which indirectly indicated that the starch and Cl - In other words, the interaction between starch and Zn 2+ The lowest interaction between Zn and Mg during charge-discharge cycling can impart 2+ The facile dynamic adsorption / desorption process does not significantly affect the Zn-I FB system, which is mainly composed of Zn 2+ Driven mass transfer process.
[0120] Go to Figure 3F , with I3 - The long-chain polymer starch unit is characterized by the I5 - The binding energy of the polyiodide species (-0.66 eV) is larger, indicating that the amylose configuration can induce a strong interaction between starch and iodine species, and starch can therefore form a more stable association with the I5-active species.
[0121] Go to Fig. 20 , showing the electrostatic potential (ESP) mapping of starch molecules. The distribution of positive and negative charges reveals that the regions near the hydroxyl regions of starch have more negative ESP values, which are considered to be strong electron-donating centers for chemical interactions. At the same time, as a Lewis acid, iodine atoms can easily react with electron-rich molecules through a charge transfer mechanism to form strong chemical adsorption complexes. Therefore, the hydroxyl network can form stable IS colloids through strong chemical adsorption, thereby verifying the colloidal chemistry with aggregation effect.
[0122] Example 6 - Electrochemical performance analysis of zinc-iodine-starch flow battery (Zn-IS FB)
[0123] The configuration of the Zn-IFB cell assembly is as follows. The polytetrafluoroethylene (PTFE) frame serves as the flow channel to fix the geometric area of 4.0 cm 2 (2×2cm 2 ) or 25cm 2 (5×5cm 2), the positions of the pre-processed three-dimensional electrodes with a thickness of 2.0 mm. Carbon felt (CF) was used as both the positive electrode and the negative electrode. To make a flow mode battery, a peristaltic pump (Chuang Rui Precision Pump) was used to circulate the electrolyte through the electrodes.
[0124] The configuration of the Zn-IS FB battery cell assembly is as follows. The iodine-starch (IS) colloid obtained from Example 3 is used as the cathode electrolyte of the Zn-I flow battery system. The system contains a cathode side, an anode side and a separator, which allow reversible electrochemical reactions to occur during the charge and discharge cycles. The cathode side has an electrode material and a first storage tank providing a cathode electrolyte. The cathode electrolyte contains 2M ZnI2 dissolved in deionized water, and the anolyte is prepared by deionized water containing 2M ZnCl2. The presence of zinc iodide ensures high charge capacity and stability, while soluble starch acts as a stabilizer and promotes the formation of aggregated colloidal nanoparticles in the electrolyte. On the anode side, the electrode material and the second storage tank provide the anolyte. The exact composition of the anolyte can vary based on the specific application and requirements of the flow battery system. The separator positioned between the cathode and the anode acts as a physical barrier to prevent direct contact between the cathode electrolyte and the anolyte. The separator must have suitable ionic conductive properties to allow ions to migrate between the two sides during the charge and discharge process. Additionally, the separator should exhibit good chemical and mechanical stability to ensure extended battery life and maintain consistent performance over multiple cycles.
[0125] To facilitate the continuous flow of anolyte and catholyte between the cathode and anode sides, a peristaltic pump may be utilized. This pump employs a cyclic compression and relaxation mechanism that causes the electrolyte solution to flow through the flow battery system. The peristaltic pump ensures a controlled and consistent flow rate, thereby contributing to the reliable operation and energy output of the battery.
[0126] Aggregated colloidal nanoparticles present in the catholyte facilitate more uniform and efficient electrochemical reactions during discharge and charge cycles. These nanoparticles prevent dendrite formation and help maintain a stable electrode-electrolyte interface, thereby improving the overall cycle life of the flow battery system. Electrochemical performance data were collected to evaluate the effect of colloidal electrolytes on the enhanced performance of the 2×2 cm 2 Effect of flow battery cells on the cycling performance of Zn-I2 flow batteries ( Fig.21 ).like Fig.22A and Fig.23As shown in Table 1, the flow mode Zn-IS FB using PP membrane (2 ml of 2 M ZnI2 containing 1 M starch||8 ml of 2 M ZnCl2 at 30 mAh) exhibited superior rate cycling and performance. -2 These cells exhibit high coulombic efficiency (CE), voltage efficiency (VE), and energy efficiency (EE).
[0127] Table 1 - Coulombic efficiency (CE), voltage efficiency (VE) and energy efficiency (EE) of Zn-IS FB at different densities
[0128] Specifically, the CE of the Zn-IS FB gradually improves with increasing current density, always maintaining a high level above 98%. This indicates that the permeability of the polyiodide active materials in the Zn-IS FB is limited during fast charging. In addition, after switching the current density back to 7.5 mA cm -2 Afterwards, the EE of the Zn-IS FB recovered to 86%, thereby indicating that the colloidal starch-based battery cell has excellent reversibility at different rates.
[0129] In addition, the corresponding voltage curves of the Zn-IS FB using PP film are shown in Fig. 22B As shown in Figure 5, a relatively low voltage polarization is revealed, which is attributed to the high ionic conductivity of the porous PP membrane and the starch-based colloidal electrolyte used in the Zn-ISFB.
[0130] Colloidal starch in the electrolyte can prevent iodide / polyiodide from coating the electrodes and thus promote the electrochemical reaction. Fig.24 As shown, using conventional Nafion membrane (N117), Zn-IFB without starch integration showed I x - The PP membrane-based Zn-ISFB of the present invention can deliver a high power density of 41.58 mW cm -2 , with a relatively low power density of 28.41 mW cm -2 Compared with the Zn-IFB based on N117 film, it shows higher power ( Fig. 22C ).
[0131] In addition, based on Fig.25 The electrochemical impedance spectroscopy (EIS) results show that the total internal resistance is 1.07 Ω cm 2The obtained porous PP film-based Zn-I FB has a lower total internal resistance (0.91 Ωcm) than the N117-based FB. 2 ). Therefore, utilizing the colloidal catholyte with a porous PP membrane leads to the superior performance of the Zn-I FB compared to that of the N117-based FB.
[0132] In addition, the internal resistance of the Zn-IS FB was tested in direct current (DC) mode to present the actual resistance under actual working conditions, which is different from the EIS results obtained under alternating current (AC) test conditions above. Based on the changes in the fitted polarization voltage at different DCs, it can be confirmed that the internal resistance of the starch-containing Zn-ISFB system using a porous membrane is smaller than that of the starch-free FB using the N117 membrane. Therefore, the porous PP membrane enabled by the colloidal cathode electrolyte can give the Zn-I FB superior performance compared to the N117-based FB. The Zn-I FB based on the N117 membrane and the developed Zn-IS FB show similar discharge capacity retention rates at different rates, indicating that the interpenetration of the multi-iodide active materials is suppressed during the cycle due to the size screening effect of the colloidal starch.
[0133] The cycling performance of Zn-IS FB at high current density and high volumetric capacity was evaluated. Fig.22D , Zn-IS FB at 30 mA cm -2 The 6Ah L2 cell exhibited stable charge-discharge operation over 350 cycles at a high current density of 1.3 Å, thereby achieving a high Coulombic efficiency (CE) of 98.5%. Notably, this performance allowed the realization of a 6Ah L2 cell. -1 阴极电解液 At the same time, the high volumetric capacity (33.5Ah L) of 50% iodine utilization (i.e., 50% SOC) was achieved. -1 阴极电解液 ), the Zn-ISFB flow system of the present invention can exhibit a long cycle calendar life (over 250 cycles) and a high current density at 22.5 mA cm -2 High CE (about 95%) under ( Fig.22E ), indicating effective suppression of the interpenetration problem of iodine species. Under the same working conditions, the PP membrane-based flow battery in a blank electrolyte without starch showed a poor CE of about 65%, which was manifested by a severe capacity loss of about 25 Ah L -1 阴极电解液 The lower discharge capacity and shorter cycle life (about 50 cycles) due to severe cross-linking and short circuiting ( Figures 26A-26C ).
[0134] refer to Fig.27A-D, the results show that under high current density conditions, the Zn-I FB based on N117 fails in a short period of 150 hours. This failure is attributed to the significant byproducts produced by severe side reactions, which lead to increased overpotential and short circuit caused by dendrites, thus causing performance fluctuations after only 42 cycles. Side reactions during battery cycling are identified as another key issue that significantly affects battery stability.
[0135] The catholyte containing small-sized starch particles was able to migrate into the anolyte, which formed a colloidal electrolyte to some extent. The life of the Zn-based asymmetric FB containing colloidal starch was extended by 240 h (340 cycles), with a peak charge / discharge rate of 10 mAh cm -2 At 30mA cm -2 The CE under the Zn electrolyte is as high as 99.01%, which is much longer than that of the asymmetric FB in the blank electrolyte (over 150 h, where the CE is as low as 98.23%), which is caused by the soft shorting caused by the side reactions and Zn dendrites.
[0136] Furthermore, the pH of the blank electrolyte increased from 4.42 to 4.75 after 70 h of operation and reached 5.13 after 140 h of operation, which was attributed to the excessive side reactions in the blank electrolyte, thereby leading to the poor reversibility of the Zn metal anode. In contrast, the Zn-IS FB with starch-based electrolyte maintained a stable pH value throughout the extended cycle of Zn-IS operation.
[0137] As shown in Figure 28, the SEM image of the carbon felt (CF) on the Zn anode side during the discharge state exhibits an irregular and mossy morphology with a rough surface. This phenomenon can be attributed to the hydrogen evolution reaction, which increases the pH of the ZnCl2 anolyte and produces byproducts such as Zn5(OH)8Cl2H2O and ZnO, as verified by the XRD results ( Fig.29 ). In contrast, a smooth and clean surface was observed on the anode current collector after the same cycle. This observation can be attributed to the ultra-small size of colloidal starch that crosses the membrane to the anolyte and thus stabilizes the pH of the anolyte, thereby conferring improved reversibility to the Zn anode.
[0138] Referring to Figures 30-31, after cycling in the starch-based colloidal electrolyte, the SEM images and XRD patterns of the PP membranes showed a cleaner surface compared to the membranes after cycling in the blank electrolyte. In addition, the N117-based Zn-IFB in the blank electrolyte also showed severe side reactions with dead dendrites and significant byproducts on the Zn anode side ( Fig.32-34). Therefore, the utilization of starch-based colloid chemistry not only enables higher operating current and higher energy for the iodine cathode side, but also enhances the cycling stability of the Zn anode side, thereby improving the overall performance of the Zn-ISFB system.
[0139] Example 7 - Preparation of a renewable solar energy storage system
[0140] To demonstrate the potential application of starch-based colloidal electrolytes in outdoor flow battery systems, the electrochemical performance of Zn-ISFBs at high temperatures was characterized, where both the reservoir and the battery cell were maintained at 50 °C.
[0141] For the high temperature of 50℃ x - Permeability, colloidal starch can strongly confine polyiodides by forming colloidal aggregates with low Ix-permeability, thereby preventing cross-penetration problems even under harsh conditions of high temperature.
[0142] like Figures 35A-35B and Fig.36 As shown in Table 2, the Zn-IS FB using PP film (2 ml of 2 M ZnI2 containing 1 M starch || 8 ml of 2 M ZnCl2 at 30 mAh) at high temperature (50 °C) exhibited a wide range of stable cycling power capabilities with high CE, VE, and EE.
[0143] Table 2 - Coulombic efficiency (CE), voltage efficiency (VE) and energy efficiency (EE) of Zn-ISFB at different densities at high temperature of 50 °C
[0144] It is worth noting that a high CE is shown in the initial cycle of the battery, and then slightly decreases with the increase in the number of cycles, which may be attributed to the oxidation of I- by air under high temperature conditions during the initial flow process, thereby acting as an active species that supplies the discharge capacity. In addition, the volumetric capacity increases with the increase in the number of cycles. This is due to the Zn that is not dissolved at high temperatures. Those Zn can be further dissolved and provide supplementary Zn metal for subsequent cycles to improve CE.
[0145] In addition, the Zn-IS FB still delivered a high power of 70.12 mW cm due to the smaller polarization with high ionic conductivity at high temperature. -2 ( Fig.35C ). At a high temperature of 50°C and a high current density of 30 mA cm -2 In the charging mode, the Zn-ISFB can adapt to more than 200 cycles of stable cycling operation with a CE as high as 98.9% ( Fig.35D). In addition, when the high volume capacity is 35.5AhL -1 When operated at room temperature, the Zn-IS FB based on colloidal chemistry exhibits superior cycling stability over 200 cycles with a considerable CE (about 91%) and 32.4 AhL at 50 °C. -1 discharge capacity.
[0146] Cycling and charge / discharge curves of Zn-I FB without starch colloid in cathodic electrolyte are shown in Figure 2. Figures 37A-37C In sharp contrast, at the same charge capacity and temperature, it exhibits unstable cycling characterized by fluctuations and low CE (less than 40%), low volumetric capacity (about 18 AhL -1 阴极电解液 ). The Zn-IS FB based on colloidal catholyte showed significantly higher CE and superior cycling stability. Such superior performance can be attributed to the IS colloid effectively suppressing the cross-penetration problem through the size screening effect on the cathode side and alleviating the hydrogen evolution and Zn dendrite problems on the anode side.
[0147] refer to Fig.38 , PTFE is used as end plates and is fixed with screws. Then, a PTFE frame is installed as a liquid flow channel. Next, the carbon felt is placed in the PTFE chamber. After that, the membrane is installed and the PTFE frame, carbon felt, PTFE end plates are assembled in sequence and finally fixed with nuts. Subsequently, the battery system is connected to a peristaltic pump and all interfaces are connected using PTFE connectors. The superior performance of Zn-IS FB enables further study of its potential for storing renewable energy from solar energy. With the expansion of membrane area (25cm 2 Battery cell size, Fig.38 )’s scaled-up Zn-IS FB was successfully integrated with solar photovoltaic panels.
[0148] In this example, a Zn-I FB battery cell group (25 cm 2 , 5.0×5.0cm 2 ) is integrated into wind and photovoltaic power generation systems. During Zn-I FB operation, a battery management system was not used to control each individual Zn-I FB to demonstrate the operating flexibility of the Zn-IFB under fluctuating charging voltage. The output of the photovoltaic cell is connected to the input of the ultra-low power DC-DC boost converter bq25504EVM with a 2V constant voltage, and the Zn-I FB battery cell group is connected to the output of the converter for charging. The sunlight intensity is collected and measured by the sunlight detector Sanliang-PP730. The output current is collected by CHI measurement.
[0149] The controller detects the solar energy intensity and the corresponding solar energy-current conversion data for one day. Fig.39A As shown in , the output current of the solar cell stack, i.e., the charging current of the Zn-IS FB, starts to rise after sunrise at 6:00 a.m. It is close to 0.3 A and remains constant from about 12:00 to 15:00 p.m., and decreases after sunset (18:30 p.m.). The fluctuation of the charging current can be attributed to the instability and intermittency of the solar energy intensity. In general, the energy conversion process is completed by converting solar energy into electrochemical energy in the Zn-ISFB. Then, the Zn-ISFB is switched to the discharge mode, which is discharged at 20 mA cm -2 The capacity of 0.496Ah and the energy of 0.535Wh can be delivered under the condition of 1.5A, which reveals the practical application of Zn-ISFB as a power source. Fig.39B ).
[0150] Impressively, the Zn-ISFB successfully powered the ‘energy’ sign comprising 280 green LED lights. Notably, the temperature reached nearly 45.8°C (data was recorded in South China) during the midday hour at 2:00 pm. The successful integration of the Zn-IS FB battery module with the photovoltaic cell panel demonstrates its high suitability as a large-scale energy storage system in future smart grids.
[0151] Example 8 - Cost Analysis
[0152] The installation cost of a flow battery unit is one of the most critical factors in determining the commercialization potential of the demonstrated system. The present invention economically calculates the installation cost of building a 1-MW zinc-iodine flow battery stack based on Nafion 117 membrane and PP membrane with colloidal electrolyte, such as Figures 39D-39E Based on the long-term performance of Zn-IFB, the power density of a typical N117-based FB is 19.95 mW cm -2 , while the developed PP-based FB has a high conductivity at 22.5 mA cm -2 The power density is 26.55mWcm -2 The simulated output of the 1-MW system requires a stacked membrane area of 5012m 2 N117 membrane and 3766m 2 PP film system ( Fig. 22C ). Therefore, the required stacked membrane area for the simulated output 1-MW system is: 3520m for N117 membrane 2 , and for PP membrane system is 2405m 2 Detailed costs and component quantities for a 1-MW flow battery cell stack are provided in Table 3.
[0153] Table 3 - Components and costs of a 1MW zinc-iodine flow battery stack Note: According to Fig. 22C The power density of the Zn-I FB based on N117 film is 28.41 mW cm -2 The working temperature of 1MW Zn-I FB is about 3519.887m 2 The stacking area of PP film was 41.587 mW cm -2 To operate 1MW Zn-ISFB, only about 2404.598m 2 All components are calculated based on the average of the 2014 future state estimates.
[0154] In Table 3, Nafion membrane has the highest cost share (88.49%, $500 / m 2 ), which results in a high installation cost for the full cell unit, with the installation cost of a 1-MW cell unit reaching $1.97 million. In contrast, by replacing the Nafion 117 membrane with a PP membrane, the cost of a 1-MW flow stack is significantly reduced by 90.02% in the installation cost, resulting in a cost reduction of $280,000.0, i.e., 14.3 times. Such a significant difference can be attributed to the lower proportion of membrane cost in the Zn-IS FB (13.32%, $10 / m 2 ), indicating that the reduced membrane cost can significantly reduce the installation cost of flow batteries in practical applications. The price of the simulated Zn-IS stack (total $636,013.00) in a 1-MWh energy storage system is lower than the price of the N117-based Zn-IFB stack (total $3,184,189.00). Therefore, it can be foreseen that additional optimization of flow battery components based on colloidal chemistry can advance the revival of the next generation of zinc-based flow batteries, which have power cost-effectiveness and significant energy density for grid-scale energy storage applications in future hot climates.
[0155] In summary, the present invention introduces a novel colloidal chemistry characterized by starch-based size-sieving effect to enhance the selectivity of polyiodides, thereby enabling the use of low-cost porous PP membranes as LPPMs with superior ionic conductivity for Zn-I FBs. This advancement promotes high operating current, high power operation, and stable cycling of PP membrane-based Zn-IS FBs. As a result, Zn-IS FBs with colloidal catholyte can maintain 37.5 mA cm -2 High current density, 42mW cm -2The power density is as high as 98.5%, the Coulombic efficiency is as high as 98.5%, and the cycling stability is as high as 350 cycles.
[0156] In addition, the colloidal Zn-IS FB system developed in this invention exhibited stable cycling over 250 cycles, even at high temperature conditions (50 °C) at 32.4 Ah L -1 This was also true at a high volumetric capacity of (50% SOC). This result was attributed to the effective size sieving under strong chemisorption promoted by the starch-iodine complex. Additionally, the applied starch colloid improved the reversibility of the Zn anode and enhanced the cycling stability of the Zn-IS FB.
[0157] Cost simulation analysis based on a 1-MW flow battery unit revealed that the installation cost of the PP membrane-based stack was significantly lower, approximately 10.1 times lower than that of the Nafion membrane-based stack.
[0158] Furthermore, the scaled-up flow battery modules demonstrate potential integration with photovoltaic solar arrays, thereby creating an integrated renewable energy storage system. The present invention serves as a model system to explore colloidal electrolyte chemistry to develop low-cost, high-power, and high-temperature adaptable LPPM-based flow batteries, thereby making them suitable for large-scale energy storage applications.
[0159] Industrial Applicability:
[0160] Large-scale energy storage is an important technology to improve the utilization efficiency of clean and renewable energy such as wind and solar energy. Among various options, flow batteries with low cost and high power are considered to be one of the most promising candidates in large-scale energy storage systems. Aqueous zinc-iodine flow batteries (Zn-IFBs) show great potential in such storage systems due to their low cost, high safety and high energy density. The present invention develops an iodine-starch (IS) cathode electrolyte system that achieves high ion selectivity and ionic conductivity, thereby enabling it to be seamlessly integrated with porous membranes, and exhibits excellent reversibility and superior performance in Zn-I FBs.
[0161] In addition, based on the cost incentive analysis of a 1-MW flow stack of Zn-I FB, it was found that Nafion membrane accounted for the highest cost (91.7%, $500 / m 2 ), resulting in a high installed cost of about $1.97 million for a 1-MW battery unit. However, by replacing the Nafion 117 membrane with a PP membrane, the cost of a 1-MW flow stack was significantly reduced by 93.2% to $130,000, which is about a 14.3-fold reduction in cost. This significant difference can be attributed to the lower proportion of membrane cost in the IS electrolyte-based Zn-IFB (18.2%, $10 / m2 ), indicating that the use of the present invention in practical applications can significantly reduce the installation cost of flow batteries.
[0162] definition
[0163] Throughout this specification, unless the context requires otherwise, the word "comprise" or variations such as "comprises / comprising" will be understood to imply the inclusion of the stated integer or groups of integers but not the exclusion of any other integer or groups of integers. It should also be noted that in this disclosure and particularly in the claims and / or paragraphs, terms such as "comprises / comprised / comprising" may have the meaning ascribed to them in U.S. patent law such that they allow for elements not expressly recited but exclude elements found in the prior art or elements that affect the basic or novel characteristics of the invention.
[0164] In addition, throughout the specification and claims, unless the context requires otherwise, the word "include" or variations such as "includes / including", will be understood to imply the inclusion of a stated integer or groups of integers but not the exclusion of any other integer or groups of integers.
[0165] References in this specification to "one embodiment", "an embodiment", "example embodiment", etc. indicate that the described embodiment may include a particular feature, structure, or characteristic, but not every embodiment necessarily includes the particular feature, structure, or characteristic. In addition, such phrases do not necessarily refer to the same embodiment. Further, when a particular feature, structure, or characteristic is described in conjunction with an embodiment, whether or not explicitly described, it is considered to be within the knowledge of those skilled in the art to affect such feature, structure, or characteristic in conjunction with other embodiments.
[0166] Other definitions of selected terms used herein can be found in the detailed description of the entire invention and application. Unless otherwise defined, all other technical terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention belongs.
[0167] Those skilled in the art will appreciate that, in light of these teachings, alternative embodiments may be implemented without undue experimentation or deviation without departing from the spirit or scope of the invention as described in the appended claims. The present invention is limited solely by the following claims, which, when considered in conjunction with the above description and drawings, encompass all such embodiments and modifications.
Claims
1. A rechargeable aqueous Zn||IS flow battery system, characterized in that The rechargeable aqueous Zn||IS flow battery system comprises: a cathode side comprising an electrode material and a first storage tank providing a catholyte, wherein the catholyte comprises zinc iodide and a soluble starch, thereby forming an electrolyte having aggregated colloidal nanoparticles; an anode side, the anode side comprising the electrode material and a second storage tank providing an anolyte; and a separator positioned between the cathode and the anode, wherein the anolyte and the catholyte flow between the cathode and the anode via a peristaltic pump, When the rechargeable aqueous Zn||IS flow battery system is in a charging state, the electrode material on the cathode side absorbs and stores one or more ions from the cathode electrolyte, and the electrode material on the anode side absorbs and stores one or more ions from the anode electrolyte.
2. The rechargeable aqueous Zn||IS flow battery system of claim 1 , wherein the electrode material comprises carbon felt.
3. The rechargeable aqueous Zn||IS flow battery system according to claim 2, wherein the geometric area of the carbon felt is 4.0 cm 2 , and the thickness is in the range of 1-5 mm.
4. The rechargeable aqueous Zn||IS flow battery system of claim 1, wherein the average diameter of the aggregated colloidal nanoparticles is in the range of 120-140 nanometers.
5. The rechargeable aqueous Zn||IS flow battery system of claim 1 , wherein the anolyte comprises zinc chloride.
6. A rechargeable aqueous Zn||IS flow battery system according to claim 1, wherein the cathode electrolyte is prepared with 2M ZnI2 and 0.1 to 2M soluble starch dissolved in deionized water, and the anolyte is prepared with deionized water containing 2M ZnCl2.
7. The rechargeable aqueous Zn||IS flow battery system of claim 1, wherein the separator comprises a porous polypropylene membrane.
8. The rechargeable aqueous Zn||IS flow battery system of claim 1, wherein the rechargeable aqueous Zn||IS flow battery system further comprises a PTFE end plate, a PTFE chamber, a PTFE gasket, a PTFE liner, a PTFE tube, a carbon plate, and a Ti foil.
9. The rechargeable aqueous Zn||IS flow battery system according to claim 1, wherein the total internal resistance of the rechargeable aqueous Zn||IS flow battery system is less than 1Ωcm 2 .
10. The rechargeable aqueous Zn||IS flow battery system of claim 1, wherein the power density of the rechargeable aqueous Zn||IS flow battery system is at least 40 mW cm -2 .
11. The rechargeable aqueous Zn||IS flow battery system according to claim 1, wherein the rechargeable aqueous Zn||IS flow battery system has a current density ranging from 7.5 to 30 mA cm at room temperature. -2 The invention discloses a novel nanostructured carbon nanotube having a coulombic efficiency of at least 94%, a voltage efficiency of at least 75% and an energy efficiency of at least 74% at a current density of 100 Å.
12. The rechargeable aqueous Zn||IS flow battery system according to claim 1, wherein the rechargeable aqueous Zn||IS flow battery system has a flow rate in the range of 7.5 to 30 mA cm at an elevated temperature of 50°C. -2 The invention discloses a novel nanostructured carbon nanotube having a coulombic efficiency of at least 90%, a voltage efficiency of at least 75% and an energy efficiency of at least 74% at a current density of 100 Å.
13. The rechargeable aqueous Zn||IS flow battery system according to claim 1, wherein the rechargeable aqueous Zn||IS flow battery system is 100 mA cm -2 The cycle stability of 350 cycles was achieved.
14. The rechargeable aqueous Zn||IS flow battery system according to claim 1, wherein the rechargeable aqueous Zn||IS flow battery system is 32.4Ah L at an elevated temperature of 50°C. -1 The cycling stability of 200 cycles was achieved at a high volumetric capacity.
15. A wind power and photovoltaic power generation system, characterized in that: The wind and photovoltaic power generation system comprises the rechargeable aqueous Zn||IS flow battery system according to claim 1.